34 Extended Effects of Sequential Weaning and Backgrounding Management in Beef Calves. (8th March 2022) - Justice, Maggie M; Mullenix, M Kim; Tigue, Alex A; Carrell, Russell C; West, Micayla H; Rodning, Soren P; Chamorro, Manuel
Abstract: Alternate weaning methods and backgrounding periods are strategies to reduce calf morbidity and mortality at feedlot arrival. The objective of this study was to assess the collective effects of weaning and post-weaning management practices on potential carryover effects on calf health and performance through the backgrounding phase. A total of 216 steer calves (average BW, 298 kg) from three Auburn University research farms were randomly assigned to one of three different weaning method groups: Fenceline weaning, nose-flap weaning, or abrupt weaning. Calves were weighed on d 0 and d 14 post weaning, and then began a 60-d preconditioning period. Calves were randomized according to previous weaning management, farm of origin, and body weight to one of three nutritional management strategies in a 3 ×3 factorial design: cool-season baleage (oats, ryegrass and crimson clover) and 1% BW dried distillers grains (DDGS), bermudagrass hay and 1% BW DDGS, or grazing mixed warm-season annuals and 1% BW DDGS. Calf body weights were collected on d 0, d 30 and d 60 of the backgrounding phase. Weights did not differ during the weaning phase but calves in the fenceline group had the greatest average daily gain (1.13 kg/d; P < 0.0001) during this phase. There was a weaning × backgrounding treatment interaction (P = 0.0097) for average daily gain during the first 30 d of the backgrounding phase. Calves that were fenceline weaned and on the cool season baleage diet had the highest average gain at 1.02 kg/d, whereas abruptly weaned calves on the grazing diet only gained 0.29 kg/d in the first 30 d. Steers on the cool season baleage diet had the greatest total gain (P < 0.0001) at 45.8 kg over the course of the 60-d period. These results indicate that backgrounding diet, coupled with weaning management strategies, may influence calf performance during the transition period for calves into the post-weaning phase.